Platinum Nanocatalysts Supported on Defective Hollow Carbon Spheres: Oxygen Reduction Reaction Durability Studies - Mashindi, Victor; Mente, Pumza; Phaahlamohlaka, Tumelo N.; Mpofu, Nobuhle; Makgae, Ofentse A.; Moreno, Beatriz D.; Barrett, Dean H.; Forbes, Roy P.; Levecque, Pieter B.; Ozoemena, Kenneth I.; Coville, Neil J. (Frontiers in Chemistry, 2022)
The durability and long-term applicability of catalysts are critical parameters for the commercialization and adoption of fuel cells. Even though a few studies have been conducted on hollow carbon spheres (HCSs) as supports for Pt in oxygen reduction reactions (ORR) catalysis, in-depth durability studies have not been conducted thus far. In this study, Pt/HCSs and Pt/nitrogen-doped HCSs (Pt/NHCSs) were prepared using a reflux deposition technique. Uniform Pt particles were formed with deposition on the outside of the shell and inside the pores of the shell. The new catalysts demonstrated high activity (> 380 µA cm-2 and 240 mA g-1) surpassing the commercial Pt/C by more than 10%. The catalysts demonstrated excellent durability compared to a commercial Pt/C in load cycling, experiencing less than 50 % changes in the mass-specific activity (MA) and surface area-specific activity (SA). In stop-start durability cycling, the new materials demonstrated high stability with more than 50% retention of electrochemical active surface areas (ECSAs). The results can be rationalised by the high BET surface areas coupled with an array of meso and micropores that led to Pt confinement. Further, pair distribution function (PDF) analysis of the catalysts confirmed that the nitrogen and oxygen functional groups, as well as the shell curvature/roughness provided defects and nucleation sites for the deposition of uniform Pt nanoparticles. The balance between graphitic and diamond-like carbon was critical for the electronic conductivity and to provide strong Pt-support anchoring.